2012
DOI: 10.1002/app.36225
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly(ethylene glycol)‐b‐poly(ε‐caprolactone) copolymers with functional side groups on the polyester block

Abstract: This study reports the successful synthesis of amphiphilic MPEG-b-PCL based-block copolymers bearing benzyloxy and hydroxyl side groups on the PCL block by ring-opening polymerization of 4-benzyloxy-e-caprolactone (4-BOCL) and e-caprolactone (e-CL) with methoxy PEG (550 g mol À1 ) as the initiator and Tin(II) 2-ethylhexanoate (SnOct 2 ) as the catalyst. These copolymers were characterized by differential scanning calorimetry (DSC), 1 H NMR, and gel permeation chromatography. The thermal properties (T g and T m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The other observation shows that when the length of hydrophilic segment(s) was increased ( I vs II and V vs VI ), which was related to higher CAC values, a larger nanoparticles were obtained (66.1 vs 89.8 nm and 49.7 vs 153.4 nm, respectively). The entrapment of drug inside the core results in the increase of hydrodynamic diameter, with the exception of sample VI, where smaller size of loaded nanoparticles may be explained by reduction of hydrophilic/hydrophobic repulsion of PCL, leading to the contraction of the core . The polymer/drug initial weight ratio also influences the particle size, which in the case of IMC‐loaded VIII is correlated to the formation of larger particles at higher ratio, but for QUE‐loaded IV opposite interaction of polymer–drug is indicated due to different nature of drug.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The other observation shows that when the length of hydrophilic segment(s) was increased ( I vs II and V vs VI ), which was related to higher CAC values, a larger nanoparticles were obtained (66.1 vs 89.8 nm and 49.7 vs 153.4 nm, respectively). The entrapment of drug inside the core results in the increase of hydrodynamic diameter, with the exception of sample VI, where smaller size of loaded nanoparticles may be explained by reduction of hydrophilic/hydrophobic repulsion of PCL, leading to the contraction of the core . The polymer/drug initial weight ratio also influences the particle size, which in the case of IMC‐loaded VIII is correlated to the formation of larger particles at higher ratio, but for QUE‐loaded IV opposite interaction of polymer–drug is indicated due to different nature of drug.…”
Section: Resultsmentioning
confidence: 94%
“…The studies on micellization of PCL copolymers with hydrophilic segments of poly(ethylene oxide), and poly(dimethylamino)ethyl methacrylate are widely reported in literature. It was shown that the variation of the copolymer's composition provided an opportunity to modify thermodynamic and kinetic stability, degradability, or release properties of the resulting micelles/aggregates . In aqueous solution, the hydrophobic character of the core enables incorporation of poorly water soluble drugs, for example indomethacine (IMC) or quercetin (QUE), into its interior by covalent or noncovalent bonding through hydrophobic interactions, making use of experimental methods such as dialysis, salting out procedure or the solvent evaporation method …”
Section: Introductionmentioning
confidence: 99%
“…Chen and coworkers presented a study of amitriptylineencapsulating triblock copolymers with PEG, M6, and M1. 44 Partial debenzylation of the M6 units generated hydroxylcaprolactone units in the core, shown in Scheme 4(d). For the triblock copolymers, increasing the M6 content changed the micelle shape from spherical to spindle-shaped.…”
Section: Physical Encapsulation Of Small Moleculesmentioning
confidence: 99%
“…This finding also confirms that the spindle-like shape of PCL- b -PEG stabilized Abm-loaded nanoparticles due to the lower T g of the hydrophobic PCL block, which causes the larger degree of stretching of the poly(caprolactone) (PCL) block. Meanwhile, the degree of stretching of the PCL block is too high to support the spherical morphology [ 40 ], leading to spindle-like morphology of the FNP-NPs. In addition, it is noteworthy that the edges of the nanoparticles were not smooth.…”
Section: Resultsmentioning
confidence: 99%